Phytochemical Extraction from Mediterranean Plants: A Comparative Study of Traditional Techniques - Melro, Elodie; Jesus, Carolina F.; Duarte, Tomás; Alves, Andreia A. S.; Antunes, Filipe E.; Lindo, Margarida; Ribeiro, Daniel (Sciences of Phytochemistry, 2026)
This study investigates how solvent polarity and extraction technique influence the recovery of bioactive compounds from four Portuguese native plants: Geranium robertianum (herb Robert), Olea europaea (olive leaves), Salvia rosmarinus (rosemary) and Laurus nobilis (bay laurel). Maceration and Soxhlet extractions were performed using five solvents spanning a polarity range (methanol, ethanol, ethyl acetate, dichloromethane and hexane), followed by colorimetric phytochemical screening and extraction-yield comparison; aqueous infusion and water-based Soxhlet extraction were also assessed. Among the organic solvents tested, extraction yield increased with solvent polarity, with methanol consistently giving the highest recoveries; aqueous extraction showed species-dependent behavior. Phytochemical assays indicated a wide metabolite coverage in methanolic extracts, whereas tannins were not detected in ethanolic extracts and were only evidenced in bay laurel under less-polar conditions. GC–MS profiling of ethanolic extracts revealed distinct species-specific fingerprints dominated by fatty acids and terpenoid constituents, with Soxhlet generally enhancing late-eluting hydrophobic metabolites; rosemary was enriched in phenolic diterpenes, herb Robert and olive leaves showed a stronger contribution of carbohydrate-related compounds, and bay laurel displayed a comparatively simpler lipid/terpenoid profile. These results highlight the suitability of these Portuguese native plants as versatile sources of bioactive fractions whose composition can be selectively tuned through solvent polarity and extraction strategy.